The diagnostic process of covıd-19 in the emergency department: laboratory and ımaging methods - Guneysu,Fatih (2020)
SUMMARY OBJECTIVES The 2019 Novel coronavirus disease puts a serious burden on the health system. Therefore, the detection of particularly serious patients at an early stage is extremely important in terms of controlling the outbreak and improving the prognosis. We investigated the role of inflammatory markers studied in patients suspected of COVID-19 at an emergency department in predicting PCR and CT results. METHODS This retrospective study was carried out with 133 patients who were admitted between 13 March and 1st April 2020 with suspicion of COVID-19. The patients were divided into four groups according to CT and RT-PCR results and evaluated. RESULTS Considering all patients, no specific findings were found in the hematological and biochemical values of patients in the laboratory analyses. Although all of the results remained within the reference range, there was a significant difference in white blood cell, neutrophil, platelet, and lymphocyte values when the groups were compared [p = 0.000; p = 0.004; p = 0.022; p = 0.023]. CONCLUSION Laboratory is not specific enough in the pre-diagnosis. In addition, this result does not alter with PCR or CT positivity. However, minimal changes observed in laboratory results may be partially guiding in patients in whom both PCR and CT are positive.